Selective Inhibitors of Kv11.1 Regulate IL-6 Expression by Macrophages in Response to TLR/IL-1R Ligands - Cheryl Hunter; Tejas B. Kadakia; Dianne Cooper; Mauro Perretti; Richard C. Schwartz; Simon B. Brown (The Scientific World Journal, 2010)
The mechanism by which the platelet-endothelial cell adhesion molecule PECAM-1 regulates leukodiapedesis, vascular endothelial integrity, and proinflammatory cytokine expression in vivo is not known. We recently identified PECAM-1 as a negative regulator of Kv11.1, a specific voltage-gated potassium channel that functioned in human macrophages to reset a resting membrane potential following depolarization. We demonstrate here that dofetilide (DOF), a selective inhibitor of the Kv11.1 current, had a profound inhibitory effect on neutrophil recruitment in mice following TLR/IL-1R–elicited peritonitis or intrascrotal injection of IL-1β, but had no effect on responses seen with TNFα. Furthermore, inhibitors of Kv11.1 (DOF, E4031, and astemizole), but not Kv1.3 (margatoxin), suppressed the expression of IL-6 and MCP-1 cytokines by murine resident peritoneal macrophages, while again having no effect on TNFα. In contrast, IL-6 expression by peritoneal mesothelial cells was unaffected. Using murine P388 cells, which lack endogenous C/EBPβexpression and are unresponsive to LPS for the expression of both IL-6 and MCP-1, we observed that DOF inhibited LPS-induced expression of IL-6 mRNA following ectopic expression of wild-type C/EBPβ, but not a serine-64 point mutant. Finally, DOF inhibited the constitutive activation of cdk2 in murine peritoneal macrophages; cdk2 is known to phosphorylate C/EBPβ at serine-64. Taken together, our results implicate a potential role for Kv11.1 in regulating cdk2 and C/EBPβ activity, where robust transactivation of both IL-6 and MCP-1 transcription is known to be dependent on serine-64 of C/EBPβ. Our data might also explain the altered phenotypes displayed by PECAM-1 knockout mice in several disease models.